Between Policies and Practices: The Challenges of Inclusive Education - Marcia Denise Pletsch; Geovana Mendonça Lunardi Mendes (Arizona State University, 2015)
The present paper aims to present the second edition of the Special Education Dossier: Differences, Curriculum, and Teaching and Learning. We discuss the policies and practices regarding the proposal for inclusive education in the context of elementary schools. We start with the idea that we are facing a global educational policy and as such, many local movements are triggered in states and municipalities to implement it.